International Mergers with Financially Constrained Owners - Aron Berg; Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2012)
This paper proposes a cross-border M&A model with financially constrained owners in which the identity of the buyer and seller can be determined. We show that policies blocking foreign acquisitions to protect the domestic industry can be counterproductive. Foreign acquisition can increase the domestic owners investment in growth industries by reducing their financial restrictions. This calls for a financial efficiency defense in the merger law. We also show that cross-border M&As are not only driven by effects on the merged entity, but also driven by the sellers alternative investment opportunities.
Keywords: F23; K21; L13; O12; 330; Investment Liberalization; Mergers & Acquisitions; Corporate Governance; Ownership